Patterns of High-Risk Sexual Practices and Risk of HIV Infection among Undergraduates in Ondo State, South-West Nigeria - Adedini, S.A (Ife Research Publications in Geography, 2024)
The study identified patterns of high-risk sexual behaviour among undergraduate students randomly selected in the two public universities in Ondo State, Nigeria. Findings showed that different patterns of high-risk sexual practices – multiplicity of sex partners, commercial sex practice, oral and anal sex – were prevalent. For instance, almost half of males and 40% of females had multiple sex partners, 19.4% of males and 28.9% of females were involved in commercial sex practice. Overall, almost two-thirds did not perceive themselves to be at risk of contracting HIV infection. The study concluded that failure or refusal to change from persistent high-risk sexual behaviour among the university students is linked with underestimation of risk of contracting HIV infection and not lack of knowledge of HIV infection. Therefore, for any HIV/AIDS campaign to be successful among university students, factors influencing underestimation of risk of infection must be addressed.